Strategi Pemasaran Bank Muamalat untuk Menarik Minat Masyarakat dalam Memiliki Tabungan iB Hijrah Haji - Refiana Alfiah Widayanti; Amin Awal Amarudin (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2026)
This study examines the marketing strategies implemented by Bank Muamalat Jombang branch to enhance public interest in the iB Hijrah Haji saving product. Utilizing a qualitative approach and field research methodology, data were collected through in-depth interviews and relevant literature, then analyzed using the Miles and Huberman technique. The findings indicate that the bank adopt various strategies, including strategic partnerships, personalized approaches, and the utilization of social media to reach prospective Hajj pilgrims. The primary factors influencing public interest are the ease of the registration process, recommendations from close acquaintances, and the overall level of trust in the bank. The effectiveness of these strategies is demonstrated by the increasing number of applicants and positive customer satisfaction levels. This research provides a significant contribution to the development of Sharia-based marketing strategies and digital innovation for the Islamic financial industry in Indonesia. By aligning traditional values with modern outreach, Bank Muamalat successfully bridges the gap between religious aspirations and financial planning, ensuring long-term growth and community engagement.